Effect of Rice Flour Fermentation with Lactobacillus spicheri DSM 15429 on the Nutritional Features of Gluten-Free Muffins - Maria Simona Chiş; Adriana Păucean; Simona Maria Man; Victorița Bonta; Anamaria Pop; Laura Stan; Bianca Vasilica Beldean (Tătar); Carmen Rodica Pop; Vlad Mureşan; Sevastiţa Muste (Foods, 2020)
Lactobacillus Spicheri DSM 15429 strain was used to ferment rice flour, aiming at exploiting its influence on the amino-acids, minerals, lactic acid, total phenols, and antioxidant activity of the rice sourdough and gluten-free muffins. Gluten-free muffins were prepared by using 15% rice sourdough fermented with the above strain of lactic acid bacteria and compared with rice spontaneous fermentation. Methods like LC-MS (Liquid chromatography–mass spectrometry), AA (atomic absorption), HPLC (High-performance liquid chromatography), Folin–Ciocalteu, and 1,1-Diphenyl-2-picrylhydrazyl radical scavenging activity (DPPH) were used to fulfill the aim of the study. The addition of rice sourdough fermented with LAB was reflected in the chemical composition of the final baked good, improving its amount on bioactive compounds such as amino acids, mineral bioavailability, total phenols, and antioxidant activity. Total phenols and antioxidant activity increased their amount by 70.53% and 73.70%, respectively, meanwhile, lactic acid, minerals, and amino-acids increased their values at least twice. Thus, rice fermented with Lactobacilus spicheri DSM 15429 strain could be a tool to further increase the nutritional value of gluten-free baked products.